Inovasi Edukasi Keuangan Syariah untuk Santri: Mini Bank Pesantren sebagai Model Simulasi Kompetensi di Era Digital - Ardiyanto; Nurjali; Al-Munip (SiNORA, 2025)
Pesantren, as a religious educational institution, plays a strategic role in shaping the character, economic skills, and financial literacy of santri (Islamic boarding school students). In the digital era, the ability to manage finances based on Sharia principles and digital competencies has become essential for santri to make sound, ethical, and sustainable economic decisions. This study aims to assess the effectiveness of implementing a pesantren mini bank as a competency simulation model to enhance santri’s Sharia financial literacy. A mixed-methods descriptive approach was employed, involving 50 active santri participants. Research instruments included mini bank activity observations, financial literacy questionnaires, and in-depth interviews. The findings indicate that the mini bank significantly improved santri’s financial literacy, with average scores increasing from 62% before the simulation to 85% after the program, while also enhancing digital skills, independence, and financial ethics. Furthermore, this model effectively cultivates responsible, transparent, and competent santri, ready to face modern economic challenges. The study confirms that the pesantren mini bank is an effective educational innovation that integrates theory, practice, and digital technology, and can be replicated in other pesantren to strengthen the economic competencies of young generations